Alzheimer's disease, apolipoprotein E and hormone replacement therapy. (December 2016) - Depypere, H.; Vierin, A.; Weyers, S.; Sieben, A.
Highlights: The prevalence of Alzheimer's disease is higher in women than in men. This may be the result of both the higher life expectancy of women and the loss of neuroprotective estrogen after menopause. Earlier age at menopause (spontaneous or surgical) is associated with an enhanced risk of developing Alzheimer's disease. It is therefore postulated that estrogen could be protective against Alzheimer's disease. New clinical studies are needed on the link between the administration of estrogen after the menopause, the development of Alzheimer's disease and the ApoE genotype. Abstract: Alzheimer's disease is the most frequent cause of dementia in older patients. The prevalence is higher in women than in men. This may be the result of both the higher life expectancy of women and the loss of neuroprotective estrogen after menopause. Earlier age at menopause (spontaneous or surgical) is associated with an enhanced risk of developing Alzheimer's disease. Therefore, it is postulated that estrogen could be protective against it. If so, increasing exposure to estrogen through the use of postmenopausal hormone replacement could also be protective against Alzheimer's disease. The results of the clinical studies that have examined this hypothesis are inconclusive, however. One explanation for this is that estrogen treatment is protective only if it is initiated in the years immediately after menopause. Another possibility is that the neuroprotective effects of estrogen are negated by a particular genotype of apolipoprotein E. This protein plays an important role in cholesterol transport to the neurons. Studies that have examined the link between estrogen replacement therapy, Alzheimer's disease and the E4 allele of ApoE are inconclusive. This article reviews the literature on the influence of hormone replacement therapy on the incidence and progression of Alzheimer's disease.